2016
DOI: 10.1007/s11524-016-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Social Resources and Depressive Symptoms: Longitudinal Results from the Multi-Ethnic Study of Atherosclerosis

Abstract: The ways in which a neighborhood environment may affect depression and depressive symptoms have not been thoroughly explored. This study used longitudinal data from 5475 adults in the Multi-Ethnic Study of Atherosclerosis to investigate associations of time-varying depressive symptoms between 2000 and 2012 (measured using the 20-item Center for Epidemiologic Studies Depression Scale (CES-D)) with survey-based measures of neighborhood safety and social cohesion (both individual-level perceptions and neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 38 publications
7
37
1
Order By: Relevance
“…Although we found that long-term cumulative exposure to social cohesion, safety, and social engagement destinations were not significantly associated with changes in depressive symptoms over time,[77] there was some evidence that changes to the environment were related to contemporaneous changes in depressive symptoms. Specifically, within-person increases in safety[77] and social cohesion[22, 77] were associated with decreases in CES-D. No significant association was found between changes in social engagement destinations[77] or neighborhood foreclosures and changes in CES-D(Crawford ND et al, unpublished). In other analyses neighborhood poverty and social environments were not consistently related to changes in cortisol over time [74] although these analyses were likely limited by the complexity of measuring changes in cortisol profiles.…”
Section: Select Findings To Datementioning
confidence: 90%
See 1 more Smart Citation
“…Although we found that long-term cumulative exposure to social cohesion, safety, and social engagement destinations were not significantly associated with changes in depressive symptoms over time,[77] there was some evidence that changes to the environment were related to contemporaneous changes in depressive symptoms. Specifically, within-person increases in safety[77] and social cohesion[22, 77] were associated with decreases in CES-D. No significant association was found between changes in social engagement destinations[77] or neighborhood foreclosures and changes in CES-D(Crawford ND et al, unpublished). In other analyses neighborhood poverty and social environments were not consistently related to changes in cortisol over time [74] although these analyses were likely limited by the complexity of measuring changes in cortisol profiles.…”
Section: Select Findings To Datementioning
confidence: 90%
“…[66, 7577] Living in neighborhoods with lower levels of social cohesion,[66, 76] lower densities of social engagement destinations, [77] and aesthetic quality, [76] and higher levels of neighborhood problems and violence[66, 76] was found to be associated with higher levels of depressive symptoms. Findings also documented that living in a neighborhood with a higher percentage of residents of the same race/ethnicity was associated with higher Center for Epidemiologic Studies Depression Scale (CES-D) scores in African American men, but with lower CES-D scores in Hispanic men and women, possibly reflecting the different environmental correlates of these compositional characteristics in different race/ethnic groups.…”
Section: Select Findings To Datementioning
confidence: 99%
“…Most studies have relied on two methods of measurement: objective measures of physical settings and subjective evaluations of living environments [8]. It is often the case that objective markers do not align with residents' self-reported exposure, and the latter is found to be more correlated with self-reported psychological problems, such as overstress, depressive symptoms and self-rated mental disorder [28,29]. However, the stronger health effect of environmental appraisals may be spurious.…”
Section: Built Environment Perceived Disorder and Mental Healthmentioning
confidence: 99%
“…However, our study, which used the longitudinal prediction data, indicated that community cohesion could not predict depressive symptoms. This may be because individuals have adapted to the community environment as they reside longer in their community (Moore et al, 2016). Therefore, the long-term effects of community cohesion and community threat on individual emotions are not signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…However, Moore et al (2016) found that when a person feels safer in the community, the less their depressive symptoms. Similarly, Flórez et al (2016) indicated that the more a person perceives security in their neighborhood, the less their psychological distress.…”
mentioning
confidence: 96%